WHO First Global Patient Safety Challenge: Clean Care is Safer Care, Contributing to the training of health-care workers around the globe - Kilpatrick, Claire; Allegranzi, Benedetta; Pittet, Didier (International Journal of Infection Control, 2010)
The World Health Organisation since 2005 has worked to support reduction and prevention of health care-associated infection around the globe as part of their Patient Safety Programme, primarily through the promotion of compliance with recommended hand hygiene practices. The programme of work has been multi-factorial, with a number of achievements acknowledged as well as published over this period, including most recently a systematic review of the global burden of disease attributable to health care-associated infection. An understanding of the situations within countries has been crucial in order to inform the whole programme targeted at health-care facilities, including tools and approaches to support the training and education of health-care workers. This has in part been achieved through testing of the WHO hand hygiene toolkit that was prepared to support implementation of the WHO Guidelines on Hand Hygiene in Health Care, launched in 2009. A lot has been achieved, however, WHO continues to highlight the need to sustain the momentum to support the enhancement of patient safety.